THE APPLICATION OF LEARNING MODEL COOPERATIVE TYPE TGT (T EAMS GAMES TOURNAMENT) ON LEARNING MATERIAL TO IDENTIFY HYDROLIC SYSTEM IN GRADE X MOTORCYCLE ENGINEERING SMK KARSA MULYA PALANGKA RAYA ACADEMIC YEAR 2014/2015 - Dedie; Sri Murwantini (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2015)
The instruments used in this study are: a cognitive tests Learning Outcomes, Teacher Activity Observation Sheet, Student Activity Observation Sheet and Student Response Questionnaire, and were analyzed using descriptive techniques. Results of the data analysis based on cognitive learning test on study completeness involving 32 students of Engineering of Motorcycles (TSM) in Vocational School of Karsa Mulya Palangka Raya individually with the teaching model is said to be completed because completeness percentage obtained by 100% (32 students), this indicates that the learning with the implementation of Cooperative Learning Model with type of Teams Games Tournament (TGT) reached the class completeness criteria required that is ?85%.The result after the student learning using cooperative learning model type Teams Games Tournament (TGT) on the material: to identify hydraulic system in class X Engineering of Motorcycles (TSM) SMK Karsa Mulya Palangka Raya with an average mark of 85.09% already meet the standards of KKM which is ?70, done by teachers/researchers was performed well. Based on the above results it can be concluded that the application of learning models Cooperative type Teams Games Tournament (TGT) as one alternative learning model can be used in material: to identify hydraulic systems that has been done well.